2016
DOI: 10.3727/096504016x14641336229602
|View full text |Cite|
|
Sign up to set email alerts
|

Knockdown of HVEM, a Lymphocyte Regulator Gene, in Ovarian Cancer Cells Increases Sensitivity to Activated T Cells

Abstract: Ovarian cancer is highly malignant with a gradually increasing incidence and a high mortality rate. Immunosuppression is induced in ovarian cancer, although the mechanism detail is not clear. It has been indicated that HVEM (herpesvirus entry mediator) B- and T-lymphocyte attenuator (BTLA) negatively regulates the immune responses of T lymphocytes. Here, HVEM mRNA was found to be elevated in ovarian cancer tissue samples and primary ovarian cancer cells in comparison with benign tissue samples. We then knocked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…For instance, enhancing BTLA/HVEM interaction could reduce the proliferation and differentiation of Vγ9Vδ2 T cells that are involved in tumor immune surveillance. 24 Zhang et al 8 reported that overexpression of HVEM in ovarian cancer cells inhibited proliferation and immune functions of T cells, while HVEM-silenced cancer cells had increased the number of activated T cells as well as the secretion of TNF-α and IFN-γ, which in turn promoted apoptosis of cancer cells. In general, the above data suggested that BTLA and HVEM may be important factors in the physiopathology of immune regulation and may also have an effect on tumor progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, enhancing BTLA/HVEM interaction could reduce the proliferation and differentiation of Vγ9Vδ2 T cells that are involved in tumor immune surveillance. 24 Zhang et al 8 reported that overexpression of HVEM in ovarian cancer cells inhibited proliferation and immune functions of T cells, while HVEM-silenced cancer cells had increased the number of activated T cells as well as the secretion of TNF-α and IFN-γ, which in turn promoted apoptosis of cancer cells. In general, the above data suggested that BTLA and HVEM may be important factors in the physiopathology of immune regulation and may also have an effect on tumor progression and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, carcinomas with a higher HVEM expression display lower TILs infiltration and worse prognosis. Similarly, in ovarian cancer, HVEM mRNA was up-regulated compared with nonmalignant tissues (98). Silencing HVEM on ovarian cancer cells by shRNA knock-down increased T cellinduced apoptosis of cancer cells in vitro.…”
Section: B7-h4 (Alternatively Called B7x or B7s1)mentioning
confidence: 91%
“…In our previous study, HVEM was found highly expressed in the ovarian cancer tissues compared with normal tissues [18]. Moreover, HVEM was correlated to TNM stage, lymph node metastasis and recurrence in ovarian serous adenocarcinoma [17].…”
Section: Hvem Co-expressed With Hif-1α In Patients With Ovarian Cancermentioning
confidence: 99%
“…In our previous finding, we showed that the expression of HVEM was significantly high in ovarian cancer tissues and was closely correlated to the clinical pathological features of the patient, including the clinical stage (FIGO2013), lymph-node metastasis and recurrence [17]. However, the overexpression of HVEM had no effects on the cell multiplication in normoxic ovarian cancer cells [18]. In this work, we investigated the role of HVEM in hypoxic ovarian cancer cells and the relationship between HVEM and HIF-1α by overexpressing and silencing HVEM.…”
Section: Introductionmentioning
confidence: 97%